A Rare Case of Metastatic Hepatocellular Carcinoma Masquerading as a Forehead Hematoma - Kimberly Sanders; Ashley Thomas; Carmen Isache; Anwer Siddiqi (Case Reports in Gastrointestinal Medicine)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer and can arise from any form of chronic liver disease or cirrhosis. With increasing rates of metabolic syndrome and obesity, it is not surprising that NASH is quickly becoming a leading cause of chronic liver disease and HCC in the western hemisphere (Wang and Malhi, 2018). Metastasis is usually found in advanced stages of the disease, owing to its poor prognosis. The lung, bone, and lymph nodes are the most frequent sites of metastasis (Balogh et al., 2016, and Becker et al., 2014). On the other hand, metastasis to the skin and cranium is relatively rare. Literature review reveals less than 10 reported cases in the last 10 years. Herein, we report an unusual case of a “forehead hematoma” leading to the formal diagnosis of metastatic HCC.